Marketing promotion and distribution of project within private and public sphere - Rastislav Kerul (Contemporary Economics, 2008)
The topic of marketing implementation within project management is out of interest of many authors. There are a few literature sources related to the theme. Our science interest is to analyze and outline the main possibilities of marketing conception implementation within project realization in order to make their distribution and promotion effective to reach the target groups and publics. We try to describe main basis of marketing perspective in managing projects in relation to target groups, to which the project would be defined and it would reach it directly or indirectly. The main aim of the study is to analyze the possibilities of project preparation and implementation with the support of direct and effective marketing mix with emphasis on promotion and distribution policy. The project would be seen as a product within this marketing mix and the price is not considered to be that interesting as it is given by the national law and concrete priority call. The communication policy as well as distribution strategy must be designed in relation to expectations and needs of target groups which might vary in their age, sex, life standard, demography characteristics, etc.
Keywords: 330